La garantía de la enseñanza de la religión en los estados concordatorios de Europa - Carlos Corral Salvador, S. J. (Estudios eclesiásticos, 2012)
The teaching of religion at public schools given by professors or teachers appointed by the corresponding religious denomination is neither exclusive to Spain nor to the Catholic Church. It takes place in many European States, Germanic and Latin as well as Baltic and Danubian.